The Archive of the Theban Choachyte Petebaste Son of Peteamunip (Floruit 7th Century BCE) : Abnormal Hieratic Papyrus Louvre E 3228 A-H - Heel, Koenraad Donker Van, (Papyrologica Lugduno-Batava ;, 2021)
This book is the first ever edition of an abnormal hieratic business archive from the Louvre once kept by a mortuary priest in 7th century BCE Thebes (Egypt). In addition to providing a full edition of the eight texts from this unique - and partly unpublished - archive, the author also discusses points of Late Period history, law, economics, religion, grammar, and chronology. There is also a particular focus on abnormal hieratic palaeography, thereby turning this publication into a genuine handbook for the study of the most difficult script from Ancient Egypt that will serve students for the next hundred years, offering a unique insight into the ancient Egyptian abnormal hieratic and demotic legal traditions.